2019
DOI: 10.1186/s13054-019-2644-x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of earlier antibiotic administration in patients with severe sepsis and septic shock in Japan: a descriptive analysis of a prospective observational study

Abstract: BackgroundTime to antibiotic administration is a key element in sepsis care; however, it is difficult to implement sepsis care bundles. Additionally, sepsis is different from other emergent conditions including acute coronary syndrome, stroke, or trauma. We aimed to describe the association between time to antibiotic administration and outcomes in patients with severe sepsis and septic shock in Japan.MethodsThis prospective observational study enrolled 1184 adult patients diagnosed with severe sepsis based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 31 publications
2
31
0
5
Order By: Relevance
“…In a before-and-after study conducted in patients with suspected infection in a surgical intensive care unit (ICU), Hranjec et al compared an aggressive regimen of antibiotic administration (initiation of antibiotics in all patients with suspected infection) with a conservative regimen (starting only after objective confirmation of infection), finding that the former was associated with higher mortality (OR, 2.5; 95% CI, 1.5-4.0) [7]. In addition, in a prospective observational study that enrolled 1184 adult patients diagnosed with severe sepsis and septic shock, Abe et al were unable to show a linear relationship between the timing of antibiotic administration, such as within 1 h or 3 h after sepsis recognition, and in-hospital mortality, nor a relation between time to antibiotics as a continuous variable and mortality (OR, 0.99; 95% CI 0.99-1.0; p = 0.152) [29]. In our knowledge, the only randomized controlled trial (RCT) that evaluated early antimicrobials administration in 2672 patients with suspected infection, although in a prehospital setting, failed to find an association between early administration of antimicrobials and mortality (RR = 0.95; 95% CI, 0.74-1.24) [30].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a before-and-after study conducted in patients with suspected infection in a surgical intensive care unit (ICU), Hranjec et al compared an aggressive regimen of antibiotic administration (initiation of antibiotics in all patients with suspected infection) with a conservative regimen (starting only after objective confirmation of infection), finding that the former was associated with higher mortality (OR, 2.5; 95% CI, 1.5-4.0) [7]. In addition, in a prospective observational study that enrolled 1184 adult patients diagnosed with severe sepsis and septic shock, Abe et al were unable to show a linear relationship between the timing of antibiotic administration, such as within 1 h or 3 h after sepsis recognition, and in-hospital mortality, nor a relation between time to antibiotics as a continuous variable and mortality (OR, 0.99; 95% CI 0.99-1.0; p = 0.152) [29]. In our knowledge, the only randomized controlled trial (RCT) that evaluated early antimicrobials administration in 2672 patients with suspected infection, although in a prehospital setting, failed to find an association between early administration of antimicrobials and mortality (RR = 0.95; 95% CI, 0.74-1.24) [30].…”
Section: Discussionmentioning
confidence: 97%
“…It is necessary to highlight the restriction regarding the sample size, for which it is not possible to rule out a beneficial effect, although it is important to note that our sample size is one of the largest collected prospectively in a study that shows no association between early administration of antimicrobials and mortality in patients with sepsis [7,[28][29][30][31][32]. Also, the problem of residual confounding-despite the use of the propensity score and adjustment for covariates-cannot be eliminated.…”
Section: Limitationsmentioning
confidence: 99%
“…Furthermore, Seymour et al observed that the time to the administration of antibiotics were not significantly associated with greater in-hospital mortality in a subgroup analysis that included 32610 septic patients without vasopressors [2]. Recently, Abe et al also did not find any association between earlier antibiotic administration and reduction in in-hospital mortality in 1124 patients with severe sepsis (Sepsis 2.0 criteria) admitted to ICU [15].…”
Section: Discussionmentioning
confidence: 99%
“…今回の我々の研究で1時間バンドル導入により院内死亡率が改善しなかった理由としては,過去の研究との敗血症の定義の違いやバンドル開始時間の定義の問題,ICU入室患者のみを対象としたことで,ERでの蘇生が成功してICU外の病棟に入院した患者を除外したことが考えられた。2018年に提唱された1時間バンドルではSepsis–3の定義が用いられている が,敗血症バンドルの有効性を示した多くの研究ではSepsis–3の定義は用いられておらず,結果の比較が困難な可能性が指摘されている , 。また,1時間バンドルではtime zero, つまり患者に対するバンドル介入開始時間をERでトリアージが行われた時点と定義している。しかし敗血症は急性冠症候群など時間依存性が高く発症時間や診断基準が明確な緊急疾患と違い,感染成立から発症,発症から診断の時間経過が様々,かつ,確定診断もむずかしい病態である。ERでトリアージされた時点をバンドル介入開始時間としても,患者のそれまでの経過や診断の経緯により,臨床経過が異なる可能性があり,1時間の重みが患者によって異なる可能性がある 。このように発症からER受診までの時間背景が異なる可能性があり,ERでのトリアージから1時間だけの治療のみで死亡率を改善することはむずかしいのかもしれない。また,本研究ではICU入室患者のみを対象としたため,ERでの1時間バンドルを含めた治療が奏功したことでICU以外の病棟に入院した患者,つまり1時間バンドルの恩恵を受けた患者を除外した可能性がある。…”
Section: 考  察unclassified